SOCRATES' HOUSE: A NOTE ON HORACE, ODES 1.29. (13th November 2018) - McOsker, Michael
Abstract : Odes (= Carm. ) 1.29, while perhaps 'not an important poem' (so Commager), is a jocular address to Horace's philosophically inclined friend Iccius, who is considering joining a military expedition to Arabia; the poet remonstrates playfully with him about seeking wealth while leaving behind his philosophical studies. It ends as follows (vv. 10–16):quis neget arduis pronos relabi posse riuos montibus et Tiberim reuerti cum tu coemptos undique nobilis libros Panaeti Socraticam et domum mutare loricis Hiberis, pollicitus meliora, tendis?